A sustainable monetary framework for an independent Scotland - Philip Pilkington (Levy Economics Institute of Bard College, 2014)
This September, voters in Scotland will decide whether to break away from the United Kingdom. If supporters of independence carry the day, pivotal choices that affect the scope of Scotland's economic sovereignty and its future relationship to the UK will need to be made, particularly with respect to the question of its currency. As the disaster in the eurozone makes clear, it is essential to get these arrangements right. In this policy brief, Philip Pilkington outlines a monetary framework designed to meet the macroeconomic challenges that would be faced by a newly separate Scotland. His conclusion: while it would be in Scotland's best interests to continue using the sterling in the short run, making the transition to issuing its own, freely floating currency would place the country on a more stable economic footing.
Keywords: 330